The Relationship Between Nutrient Intake (Protein, Zinc, Iron), Parenting, and Sanitary Hygiene on The Incidence of Stunting - Agustin, Elviana; Lestari, Puji; Kurniasanti, Pradipta (Nutrition Study Program, Faculty of Medicine, Universitas Negeri Semarang, Indonesia, 2024)
Introduction: Stunting is a condition where the length or height of a toddler is below his age group. This condition is measured by length or height according to age < -2 SD, which WHO has determined. This study aimed to determine the relationship between intake of nutrients (protein, zinc, and iron), parenting styles, and sanitation hygiene on the incidence of stunting. The method used is a cross-sectional study design. Methods: The research sample was 73 mothers under five. The sampling technique used is simple random sampling. The analysis used is the Pearson correlation test and multiple linear regression analysis. Results: The results of this study indicate that there is a relationship between protein intake and stunting (p-value = 0.159), zinc intake and stunting (p-value = 0.192), and iron intake and stunting (p-value = 0.365). Parenting style with stunting (p-value = 0.025) and the relationship between sanitation hygiene and stunting (p-value = 0.022). Conclusion: The most dominant variable in the incidence of stunting is sanitary hygiene (coefficient β = 0.218, p-value = 0.002).